2023
DOI: 10.3390/ijms24044133
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomal Gel for Topical Administration of Dimethyl Fumarate in the Treatment of HSV-1 Infections

Abstract: The infections caused by the HSV-1 virus induce lesions on the lips, mouth, face, and eye. In this study, an ethosome gel loaded with dimethyl fumarate was investigated as a possible approach to treat HSV-1 infections. A formulative study was conducted, evaluating the effect of drug concentration on size distribution and dimensional stability of ethosomes by photon correlation spectroscopy. Ethosome morphology was investigated by cryogenic transmission electron microscopy, while the interaction between dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This thermoreversible micellar mode of chains association ( Scheme 2 ) makes PL attractive for various applications [ 34 , 35 , 36 ]. Several studies have proposed XG-PL-based hydrogels formulations with potential applications as ophthalmic drug-delivery systems [ 37 , 38 ], buccal drug-delivery systems [ 39 ], and for topical application and administration of different active principles [ 40 , 41 , 42 ]. Injectable Pluronic hydrogels were considered suitable systems to assist local cancer treatment (for chemotherapy, phototherapy, immunotherapy, or gene therapy).…”
Section: Resultsmentioning
confidence: 99%
“…This thermoreversible micellar mode of chains association ( Scheme 2 ) makes PL attractive for various applications [ 34 , 35 , 36 ]. Several studies have proposed XG-PL-based hydrogels formulations with potential applications as ophthalmic drug-delivery systems [ 37 , 38 ], buccal drug-delivery systems [ 39 ], and for topical application and administration of different active principles [ 40 , 41 , 42 ]. Injectable Pluronic hydrogels were considered suitable systems to assist local cancer treatment (for chemotherapy, phototherapy, immunotherapy, or gene therapy).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, a previous study found that DMF improved herpetic keratitis by increasing IL-4 and IL-5 secretion, both Th2-related cytokines, by activated lymphocytes [ 81 ]. Moreover, another research group recently reported antiviral effects for DMF against HSV infections in vitro, reducing viral yields both at 1 h and 4 h post-infection [ 82 ]. Notably, this study suggests the possibility of using a DMF-loaded gel composed of ethosomes for the topical treatment of HSV-1 infections, which remains to be assessed [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another research group recently reported antiviral effects for DMF against HSV infections in vitro, reducing viral yields both at 1 h and 4 h post-infection [ 82 ]. Notably, this study suggests the possibility of using a DMF-loaded gel composed of ethosomes for the topical treatment of HSV-1 infections, which remains to be assessed [ 82 ]. Importantly, an in vivo irritation test demonstrated that this gel is safe to apply over intact human skin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with DMF (15 mg/kg) for 28 days pre-infection and 14 days post-infection with Herpes simplex Virus 1 (HSV1) improved severe keratitis by reducing corneal inflammation in mice ( Heiligenhaus et al, 2004 ). The antiviral effect of DMF against HSV1 has been recently confirmed in vitro by a study also investigating the topical use of DMF loaded in ethosome gel, which displays favourable skin tolerability and safety in human volunteers ( Sicurella et al, 2023 ). Of interest, recent in vitro evidence in human primary retinal endothelial cells showed cytoprotective and antioxidant effects of DMF under high glucose conditions, opening an interesting perspective and rationale for further evaluation of this molecule in retinal pathologies featured by vascular complications, such as diabetic retinopathy ( Manai et al, 2022 ).…”
Section: Novel Potential Pharmacological Applicationsmentioning
confidence: 92%